2009
DOI: 10.1007/s10147-009-0909-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of PSA bounce after permanent prostate brachytherapy for localized prostate cancer

Abstract: PSA bounce is not a rare phenomenon after prostate brachytherapy. It is more common in younger patients and patients receiving higher doses of radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…In this group, %UD90, UD90 and %UD30 showed a significant difference between patients with PSA bounce and those without PSA bounce, while age showed a marginal difference ( p  = 0.06). Previous studies have reported that age, D90, isotope, and prostate volume were the significant predictive factors of PSA bounce [3-9]. On the other hand, age, %UD90 and %UD30 were significant predictive parameters of PSA bounce by univariate analysis using a Cox proportional regression hazard model in this study.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…In this group, %UD90, UD90 and %UD30 showed a significant difference between patients with PSA bounce and those without PSA bounce, while age showed a marginal difference ( p  = 0.06). Previous studies have reported that age, D90, isotope, and prostate volume were the significant predictive factors of PSA bounce [3-9]. On the other hand, age, %UD90 and %UD30 were significant predictive parameters of PSA bounce by univariate analysis using a Cox proportional regression hazard model in this study.…”
Section: Discussionsupporting
confidence: 43%
“…Reportedly, 17% to 62% of patients are diagnosed with PSA bounce using several definitions [1-10]. The median time to PSA bounce varied from 15 months to 26 months [1,2,4,6,7,9,10]. The median height of PSA bounce was 0.4 ng/mL to 0.8 ng/mL [1,2,4,6-9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toledano et al reported similar results with a higher threshold, 200 Gy [32,33]. Recently, Kanai et al found in a multivariate analysis that high D90 was correlated with bounce occurrence [17]. Some have speculated that high doses could lead to a greater likelihood of inflammatory and thus to PSA bounce.…”
Section: Discussionmentioning
confidence: 88%